Cayley Bipolar Fuzzy Graphs - Noura O. Alshehri; Muhammad Akram (The Scientific World Journal)
We introduce the concept of Cayley bipolar fuzzy graphs and investigate some of their properties. We present some interesting properties of bipolar fuzzy graphs in terms of algebraic structures. We also discuss connectedness in Cayley bipolar fuzzy graphs.